2013
DOI: 10.5296/ijld.v3i1.3134
|View full text |Cite
|
Sign up to set email alerts
|

Good University Income Generating Governance in Indonesia: Agency Theory Perspective

Abstract: The objective of this study aims to comprehend and portray the management opinions of the three Public Service Board (PSB) universities in Indonesia dealing with the good university income generating governance. Furthermore, this study applies epistemological subjectivism, interpretivism paradigm with multi-site design. The findings were analyzed using agency theory perspective. Therefore, the finding results show that the principles of good university income generating governance is law-abiding, academic orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…The position of the assignee (agent) can be assumed as the structural leaders and academicians of a university. Some research on good governance in universities based on agency theory has been done by researchers [9,10].…”
Section: Agency Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The position of the assignee (agent) can be assumed as the structural leaders and academicians of a university. Some research on good governance in universities based on agency theory has been done by researchers [9,10].…”
Section: Agency Theorymentioning
confidence: 99%
“…The results show that there is no direct effect of the provision of new incentives on the academic teaching performance of the professor. A group researchers reported that the problem which is very important for universities is their highly dependence on the income sources derived from students [10]. It becomes a significant issue on the implementation of independent principles.…”
Section: Agency Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges in funding occur due to the rising costs in the university education as compared to the relatively low revenues. Income Generating Units are thus internationally practices in sourcing additional funds into the universities (Siswanto, 2013). The IGUs not only aim to bridge the capital insufficiency in the institutes of higher learning, but also improve the quality of education as well.…”
Section: Introductionmentioning
confidence: 99%
“…The financial obligation of the government is to be expanded to cover both private and public learning institutions in the way of capital expansion and supporting them in terms of budgeting. Additionally, such privileges as government scholarships, loans and bursaries shall also be made available to the private sectors (Siswanto, 2013). As in the cases with the Kenyan public universities, for the four or five years that a student will be in the university, under government regular program, they are assured that they will receive tuition funding from the government (Oketch, 2003).…”
Section: Introductionmentioning
confidence: 99%